Language Deviations in a Popular Novel: An Alternative Way to Teach Morphology and Phonology for English Department Students of Madura University - Budiharto, R.Agus (Sebelas Maret University, 2016)
Language becomes the medium in performing the works, especially literary work in written form, such asnovel. The writerâs ideas in his literary work such as novel are illustrated by language, especially by the word Â choices in creating the works. Sometimes, when the writer creates his ideas in his work, he/she uses thelanguage deviation to make his language become creative. Language deviation can be applied in Englishnovel that can be a medium for students in studying English. This paper tries to investigate the languagedeviations in popular novel Harry Potter and the Prisoner of Azkaban by J.K Rowling utilized as analternative way of teaching morphology and phonology for fourth semester students of English department inMadura University. The findings show that by using the language deviation, particularly grammaticaldeviation and phonological deviation, the students have some effects on the their mind, the effects are makingthe studentsâ mind have the funny feeling when they connect the language deviation with the familiar Englishstandard language, making them have a curious feeling when they read the novel of which the arrangement ofwords are not in order, and making them pay more attention to the story.